SYSTEM AND SYNERGETIC METHODOLOGY TO RESEARCH DOCTOR'S PROFESSIONAL COMPETENCES IN THE MULTIPROFILE HEALTHCARE INSTITUTIONS - A.H. Shevtsov (State Institution of Science «Research and Practical Center of Preventive and Clinical Medicine» State Administrative Department, 2021)
The national strategy for a new health care system formation in Ukraine requires medical institutions to comply with national and international standards of medical service quality and staff training, based on the concepts of their professional competencies, provided by undergraduate education and postgraduate training of doctors, nurses and managers.